A Catalyst‐free Synthesis of Pyrazolopyridines Derived from Alicyclic Mono‐ketones. (17th August 2016) - Wan, Yu; Huang, Shu‐Ying; Liu, Gui‐Xiang; Chen, Liang‐Feng; Yue, Shu‐Ning; Zhang, Wen‐Li; Zou, Huan; Zhang, Li‐Zhuo; Cui, Hao; Zhou, Sheng‐Liang; Wu, Hui
Abstract : Inactive alicyclic mono‐ketones (cyclohexanone and cyclopentanone) were firstly used as reactants to prepare pyrazolopyridine derivatives in good yield through their catalyst‐free reaction with 5‐aminopyrazole and aromatic aldehyde in ionic liquid. Abstract :